Daclatasvir, sofosbuvir, and ribavirin for hepatitis C virus genotype 3 and advanced liver disease: A randomized phase III study (ALLY‐3+). Issue 5 (4th March 2016) - Leroy, Vincent; Angus, Peter; Bronowicki, Jean‐Pierre; Dore, Gregory J.; Hezode, Christophe; Pianko, Stephen; Pol, Stanislas; Stuart, Katherine; Tse, Edmund; McPhee, Fiona; Bhore, Rafia; Jimenez‐Exposito, Maria Jesus; et al.
Abstract : Patients with hepatitis C virus (HCV) genotype 3 infection, especially those with advanced liver disease, are a challenging population in urgent need of optimally effective therapies. The combination of daclatasvir (DCV; pangenotypic nonstructural protein 5A inhibitor) and sofosbuvir (SOF; nucleotide nonstructural protein 5B inhibitor) for 12 weeks previously showed high efficacy (96%) in noncirrhotic genotype 3 infection. The phase III ALLY‐3+ study (N = 50) evaluated DCV‐SOF with ribavirin (RBV) in treatment‐naïve (n = 13) or treatment‐experienced (n = 37) genotype 3‐infected patients with advanced fibrosis (n = 14) or compensated cirrhosis (n = 36). Patients were randomized 1:1 to receive open‐label DCV‐SOF (60 + 400 mg daily) with weight‐based RBV for 12 or 16 weeks. The primary endpoint was sustained virological response at post‐treatment week 12 (SVR12). SVR12 (intention‐to‐treat) was 90% overall (45 of 50): 88% (21 of 24) in the 12‐week (91% observed) and 92% (24 of 26) in the 16‐week group. All patients with advanced fibrosis achieved SVR12. SVR12 in patients with cirrhosis was 86% overall (31 of 36): 83% (15 of 18) in the 12‐week (88% observed) and 89% (16 of 18) in the 16‐week group; for treatment‐experienced patients with cirrhosis, these values were 87% (26 of 30), 88% (14 of 16; 93% observed), and 86% (12 of 14), respectively. One patient (12‐week group) did not enter post‐treatment follow‐up (death unrelated to treatment). There were 4 relapses (2 per group) and no virological breakthroughs. The most common adverse events (AEs) were insomnia, fatigue, and headache. There were no discontinuations for AEs and no treatment‐related serious AEs. Conclusion : The all‐oral regimen of DCV‐SOF‐RBV was well tolerated and resulted in high and similar SVR12 after 12 or 16 weeks of treatment among genotype 3‐infected patients with advanced liver disease, irrespective of past HCV treatment experience. (Hepatology 2016;63:1430‐1441)